HELICOPTER PARENTING: Studi Kasus Konseling Pastoral Dalam Menangani Pola Asuh Helikopter - Elsye Esterina Londo; Ryanto Fadly Sumendap (Institut Agama Kristen Negeri Manado, 2022)
The family is a place where each family member grows and flourishes, a family might be likened to a house that must correlate between every aspect of the element in it. Relationships not only talk about relationships but also talk about correlation that must have a connection between each other. Family circumstances should also emphasize an awareness of the essence of each member of the family, one that must be marked by definite and precise limits on application. A single upbringing is something that has to be associated with essence and boundaries that can set a specific goal. It is essentially the goal of taking control of and fulfilling the duties of each individual inside, that love always hates the basis of the application of foster care, but understanding of excessive affection can lead to parents in providing deviant foster care such as helicopter parenting. In the study researchers would like to try to explore more deeply the matter of the care of the helicopter's helicopter pattern is supported by qualitative and cemented research approaches with a pastoral case-counseling approach. This heatophic fabrication if it is left to disrupt the stability of the family and impact on mental issues that can last personally acceptable.